Site-Selective Lewis Acid Mediated Transformation of Pseudo Glycals to 1-Deoxy-2-thioaryl/alkyl Glycosides - Tiwari, Bindu; Sharma, Manish K.; Pandey, Ram P.; Hussain, Nazar (Synthesis, 2023)
A site-selective Lewis acid mediated transformation of pseudoglycals with various thiols for the synthesis of C-2 thioaryl glycosides was developed. The substrate scope of the reaction was explored with various thiols having various functional groups on aromatic rings as well as with pseudoglycals obtained from different sugars. The compatibility and survival of various protecting groups on pseudoglycals and substituted thiols show tolerance under the reaction conditions. Finally, the potential synthetic utility of the synthesized compounds was demonstrated and also the late-stage modifications of various drugs and pharmaceuticals were also explored.
Keywords: glycals; thioglycosides; Lewis acid; transformations; pharmaceuticals